Osteoid osteoma near the intervertebral foramen may induce radiculopathy through tumorous inflammation - Komiya Setsuro; Ishidou Yasuhiro; Yamamoto Takuya; Zenmyo Michihisa; Ijiri Kosei (BMC, 2011)
Abstract Osteoid osteoma of the spine is a relatively rare bone-forming tumor. Pain that is worse at night and relieved by aspirin and muscle contracture are the most characteristic symptoms of spinal osteoid osteoma. Although radicular pain occasionally occurs in spinal osteoid osteoma, spinal cord and nerve root compression is absent in most cases. Although radicular pain appears to be associated with tumorous inflammation, there have been no presentations of histological findings of inflammation around the nerve root. We present here two rare cases of spinal osteoid osteoma causing radiculopathy and the first histological evidence of tumorous inflammation as a cause of radiculopathy in osteoid osteoma near the intervertebral foramen.